Research progress on the role of exercise-regulated reactive astrocytes in the prevention and treatment of Parkinson’s disease - Yang, Quan; Zhuang, Chunyu (Frontiers in Aging Neuroscience, 2025)
Astrocytes generally perform protective roles, such as the release of neurotrophic factors, glutamate metabolism, transfer of healthy mitochondria to neurons, and maintenance of the blood-brain barrier. Nonetheless, in the context of Parkinson’s disease (PD), astrocytes may become dysfunctional, contributing to neurotoxicity, which is intricately linked to the etiological factors of PD. Intervening to prevent the conversion of astrocytes into neurotoxic phenotypes has demonstrated neuroprotective effects, potentially averting the degeneration of dopaminergic neurons and mitigating behavioral deficits in PD model mice. Research has shown that exercise decreases the prevalence of central pro-inflammatory and neurotoxic reactive astrocytes while increasing the presence of anti-inflammatory and neuroprotective reactive astrocytes. Various forms of exercise therapy are extensively employed as adjunctive treatments alongside pharmacotherapy in PD patients, and have been empirically validated to directly enhance motor function, functional flexibility, gait, balance, fine motor skills, and overall quality of life in individuals with PD. The potential mechanism of various types of exercise therapy in improving PD-related behavioral dysfunction is closely related to the regulation of the conversion of pro-inflammatory and neurotoxic reactive astrocytes to anti-inflammatory and neuroprotective astrocytes by exercise. This paper discusses the regulatory role of reactive astrocytes in neuroinflammation and PD neurodegeneration, as well as the reduction of neuroinflammation and the progression of PD through exercise regulation of reactive astrocytes, so as to provide a theoretical basis for further exploring the pathogenesis of PD and further developing therapeutic interventions for neurodegenerative diseases.